Surgical treatment of postburn heterotopic ossification around the elbow: Three case reports. Issue 6 (February 2019) - Chen, Ji-Ying; Fu, Chun-Wei; Ho, Hsu-Yu; Lu, Yung-Chang
Abstract: Rationale: Heterotopic ossification (HO), which is defined as the formation of new bone in tissues that do not normally ossify, is an infrequent yet debilitating complication of burns. Herein, we report three patients who suffered from elbow HO after burn injury due to a dust explosion event. This is a case report that includes the most cases involved in a single mass casualty incident in the presented literature. Patient concerns: Case 1: A 28-year-old man presented with second-to-third degree 88% total body surface area (TBSA) burns after the explosion event. He complained of decreased progressive bilateral elbow range of motion (ROM) for 1.5 months after the burn injury. Case 2: A 28-year-old woman presented with second-to-third degree 50% TBSA burns and complained of decreased progressive bilateral elbow ROM with intolerable pain on elbow extension for 1 month after the burn injury. Case 3: A 22-year-old man presented with second-to-third degree 90% TBSA burns and complained of significantly decreased left elbow ROM with intolerable pain 5 months after the burn injury. Diagnosis: The follow-up radiograph of the symptomatic elbow of these three patients revealed heterotopic ossification formation. Three-dimensional reconstruction computed tomography performed preoperatively showed that HO mainly affected the humeroulnar joint. Interventions: We treated all three patients with surgical elbow HO resection and ulnar nerve transposition, followed by immediate passive ROM exercise since postoperative day 1 and continuous physical therapy. Outcomes: In case 1, the documented ROM gain on the last follow-up (18.5 months after surgery) was 30° in the right elbow and 118° in the left elbow. In case 2, the follow-up time was 21 months and the documented ROM gain on the last follow-up was 120° in the right elbow and 90° in the left elbow. In case 3, the follow-up time was 20 months and the documented left elbow ROM gain on the last follow-up was 40°. Lessons: We discuss our experience of treating postburn HO and review the recent literature. The postburn HO treatment results of early surgical excision combined with immediate postoperative physical therapy were satisfactory.